Ventilatory response to head‐down‐tilt in healthy human subjects - Abdulaziz Alsharifi; Niamh Carter; Akbar Irampaye; Charlotte Stevens; Elisa Mejia; Joerg Steier; Gerrard F. Rafferty (Experimental Physiology)
Abstract Postural fluid shifts may directly affect respiratory control via a complex interaction of baro‐ and chemo‐reflexes, and cerebral blood flow. Few data exist concerning the steady state ventilatory responses during head‐down tilt. We examined the cardiorespiratory responses during acute 50° head‐down tilt (HDT) in 18 healthy subjects (mean [SD] age 27 [10] years). Protocol 1 (n = 8, two female) was 50° HDT from 60° head‐up posture sustained for 10 min, while exposed to normoxia, normoxic hypercapnia (5% CO2), hypoxia (12% inspired O2) or hyperoxic hypercapnia (95% O2, 5% CO2). Protocol 2 (n = 10, four female) was 50° HDT from supine, sustained for 10 min, while breathing either medical air or normoxic hypercapnic (5% CO2) gas. Ventilation (V̇E, pneumotachograph), end‐tidal O2 and CO2 concentration and blood pressure (Finapres) were measured continuously throughout each protocol. Middle cerebral artery blood flow velocity (MCAv; transcranial Doppler) was also measured during protocol 2. Ventilation increased significantly (P < 0.05) compared to baseline during HDT in both hyperoxic hypercapnia (protocol 1 by mean [SD] 139 [26]%) and normoxic hypercapnia (protocol 1 by mean [SD] 131 [21]% and protocol 2 by 129 [23]%), despite no change in PETCO2 or PETO2 from baseline. No change in V̇E was observed during HDT with medical air or hypoxia, and there was no significant change in MCAv during HDT compared to baseline. The absence of change in cerebral blood flow leads us to postulate that the augmented ventilatory response during steep HDT may involve mechanisms related to cerebral venous pressure and venous outflow.